Effective thickness of gallium arsenide on the transverse electric and transverse magnetic modes - Alwan Saib Thiab; Al-Bawee Abbas; Alrubaiy Ahmed A. A. G. (Curved and Layered Structures)
The aim of this work is to investigate gallium arsenide, a particular kind of semiconductor. The study employs a three-layer asymmetric slab waveguide structure, where a thin gallium arsenide (GaAs) film is deposited on a glass substrate, and above the film is a dielectric cladding, such as air. To enable complete internal reflection at the interfaces, the guiding slab’s index of refraction has to be greater than that of the cover material (cladding) or the substrate material. Further investigated are the effects of the thickness of GaAs on transverse electric/transverse magnetic (TE/TM) propagation modes typically. Every method was shown with specific settings. The thickness of GaAs affects the number of TE/TM modes. Cut-off wavenumber and attenuation decrease for a particular applied wavelength (0.6328 µm) due to decreasing propagation wavenumber. Simulation findings clearly reveal that the basic mode has the biggest incidence angle and lowest penetration depth; the highest mode has the incidence angle very near the critical angle and the best penetration depth. The design of integrated optical devices depends on optical waveguides, which calls for consistent and accurate findings for defining the waveguide’s properties prior to manufacturing.